Morphological characterization and agronomic performances of cashew (Anacardium occidentale L.) accession from Benin - CHABI-SIKA, KAMIROU; ADOUKONOU, AWO SAGBADJA HUBERT; AHOTON, ESSÈHOU LÉONARD; ADEBO, I.; ADIGOUN, F.A.; SAIDOU, ALIOU; AHANCHEDE, ADAM; KOTCHONI, SIMEON; BABA-MOUSSA, LAMINE SAÏD (My University, 2015)
Cashew tree is a multi-purpose fruit species in Benin. The aim of this study was to evaluate the agro-morphological diversity of the cashew varieties for their better management and utilization in crop improvement. For this purpose, 120 cashew trees sampled from the three major production areas were characterized based on 36 (14 qualitativeand 22 quantitative) agro-morphological descriptors developed by Bioversity International. Statistical tools such as Principal Component Analysis (PCA) and Hierarchical Clustering Analysis (HCA) tools have been used to describe the genetic variability. PCA results revealed that the parameters related to apple, nuts, kernel and inflorescence are the most important parameters that heavily contribute to overall diversity within the cashew species. Based on HCA of the quantitative variables, four phenotypic classes were distinguished within the sampled cashew trees. Significant correlations (positive or negative) were detected between variables such as the length and weight of the apple on one hand and the weight, length and width of the nut and inflorescence on the other hand. This preliminary work suggests the existence of an important genetic variability among Beninese cashew accessions that could be used in a breeding program.
Keywords: Agro-morphology; fruit tree; phenotypic diversity